Invisible disabilities: perceptions and barriers to reasonable accommodations in the workplace - Syma, Carrye (Library management, 2019)
Purpose The subject of invisible disabilities is becoming more prevalent in the workplace. Invisible disabilities (as defined by the Invisible Disabilities Association) refers to symptoms such as “debilitating pain, fatigue, dizziness, cognitive dysfunctions, brain injuries, learning differences and mental health disorders, as well as hearing and vision impairments.” There are times when employees are hesitant to disclose their invisible disability to their employer or coworkers, which means that accommodations for disabilities may not be requested or made. Accommodations made in the workplace for invisible disabilities can include flexible schedule, special software for assisting with scheduling or prioritizing tasks, or architectural changes such as a standing desk. The paper aims to discuss these issues. Design/methodology/approach For this literature review, articles on invisible disabilities and accommodations were researched and used to support the importance of accommodations in the workplace. Findings Invisible disabilities are affecting the workplace and must be addressed. Those struggling with invisible disabilities need to consider sharing information about their disability with their employer as well as requesting accommodation. The question of whether or not to inform coworkers should be left to individual employees and what they feel comfortable divulging. More research needs to be done on how to create learning opportunities and sensitivity in the workplace to those with invisible disabilities. Perhaps training should be offered at the time a new employee begins work. Originality/value This literature review is of value because it speaks to an important issue facing today’s workplaces – invisible disabilities and accommodations. Mental illnesses are an invisible disability and as more people are diagnosed and enter the workforce, employers are faced with an increasing demand to meet the needs of these workers. Educating employers and employees on the topic of invisible disabilities and accommodations paves the way to a greater and more productive workforce.